2017
DOI: 10.2174/1874325001711011041
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Antebrachial Cutaneous Nerve as a Donor Source for Digital Nerve Grafting: A Concept Revisited

Abstract: Objective:The main objective of this study is to evaluate the availability of lateral antebrachial cutaneous nerve (LACN) autograft for acute or delayed repair of segmented digital nerve injuries.Patients and Methods:13 digital nerve defects of 11 patients; treated with interposition of LACN graft that harvested from ipsilateral extremity were included in the study. Mean follow up period was 35, 7 months. The mean time from injury to grafting is 53, 3 days. The results of the mean 2PDT and SWMT values of injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…If the trunk were transected, we recommend nerve suture or proximal nerve-end translocation to a local muscle under loupe magnification based on recommendations from orthopedic and neurosurgical articles. [9][10][11][23][24][25][26] Our study has some limitations. First, the number of enrolled patients was small.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…If the trunk were transected, we recommend nerve suture or proximal nerve-end translocation to a local muscle under loupe magnification based on recommendations from orthopedic and neurosurgical articles. [9][10][11][23][24][25][26] Our study has some limitations. First, the number of enrolled patients was small.…”
Section: Discussionmentioning
confidence: 94%
“…23,24 The most important step in their prevention is to avoid intraoperative nerve injury because even minor damage to the most peripheral nerves in the digits could lead to neuropathic pain. 9,23,25 VA surgery should ensure the preservation of the SRN, LACN, and MACN trunks to avoid the risk of extensive sensory blunting and potential neuropathic pain. If the trunk were transected, we recommend nerve suture or proximal nerve-end translocation to a local muscle under loupe magnification based on recommendations from orthopedic and neurosurgical articles.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The interconnected plexus and overlap between the LACN and the superficial radial nerve at the radial side of the distal forearm explained the result of less donor site sensory deficit; however, this was not a concern of the patients since it is a noncritical cutaneous region. 17,[29][30][31] The confusion between LABN and the radial artery perforator flap would be taken into account in the future by the cadaveric study, which separates group of limbs by excluding the LACN from the flap and thus shows differences between the LABN and the radial artery perforator flap which could be elucidated. This would actually be a completely novel study to identify differences of a neurocutaneous perforasome in the volar forearm from a purely septocutaneous perforasome.…”
Section: Discussionmentioning
confidence: 99%
“…Tank et al showed that LABCN has more similarity to the fingers' nerves in the fascicle pattern [12]. Also, some clinical trials such as Schonauer et al, Pilanci et al, and Unal et al's works elucidated that more sensory regaining chance at recipient occurred by LABCN as interposed graft and encouraged by the advantage of LABCN uptake from the nonresting area of distal lateral of forearm that makes no critical problem in the patient [24][25][26]. Since Higgins et al tried to cater a nerve graft selection guideline for the middle finger, the strong point of the present study is introducing a new practical guideline for thumb nerve defects as the main finger for gripping and the importance of its function in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Tank et al showed that LABCN has more similarity to the fingers’ nerves in the fascicle pattern [ 12 ]. Also, some clinical trials such as Schonauer et al, Pilanci et al, and Unal et al’s works elucidated that more sensory regaining chance at recipient occurred by LABCN as interposed graft and encouraged by the advantage of LABCN uptake from the non-resting area of distal lateral of forearm that makes no critical problem in the patient [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%